STUDY AHD APPLICATION OF INSECTO-ACARICIDAL PLANTS AGAINST PARASITES AND PARASITIC DISEASES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The articlediscusses various aspects of obtaining drugs against parasites andparasitic diseases based on essential oil plants of the Kyrgyz Ala-Too. Long before the appearanceof synthesized drugs, animals ate certain types of essential oil plants to get rid of various parasites.It is known that some wild and domestic animals with certain diseases eat poisonous, strongsmelling plants, the medicinal properties of which cannot yet be fully explained. As a result ofstudies of the studies plants, a pronounced therapeutic and prophylactic effect on parasitic diseaseswas shown. However, the proposed plants and their action separately for these diseases are nothighly effective. In order to enhance their preventive effect, complex recipes, doses, premixes,infusions and extracts from the studied plants were developed.
Keywords: aspects, parasites, insecticide, acaricide, parasitic diseases, essential oils, plants, prevention, action, complex, recipes, doses, infusion, extract, enhance, effectiveness.